ZnO Nanoparticles by Hydrothermal Method: Synthesis and Characterization - Juan Carlos Anaya-Zavaleta; Antonio Serguei Ledezma-Pérez; Carlos Gallardo-Vega; Joelis Rodríguez-Hernández; Carmen Natividad Alvarado-Canché; Perla Elvia García-Casillas; Arxel de León; Agustín Leobardo Herrera-May (Technologies)
The synthesis of reliable, cost-effective, and eco-friendly ZnO piezoelectric nanoparticles (NPs) can contribute to nanotechnology applications in electronics, sensors, and energy harvesting. Herein, ZnO NPs were synthesized using a hydrothermal method under varied reaction times and adding ammonium hydroxide, which provided an advantage of a low-cost, scalable, low-temperature, and environmentally friendly process. Characterization through UV–Vis spectroscopy revealed absorption peaks between 374 and 397 nm, showing a blue shift compared to bulk ZnO (400 nm) attributable to nanoscale dimensions. Transmission Electron Microscopy (TEM) analysis indicated particle dimensions with length and width ranges from 150 to 341 nm and from 83 to 120 nm, respectively. X-ray diffraction (XRD) confirmed high-crystalline quality, with crystallite sizes calculated using the Scherrer equation. In addition, the effective mass model provided an estimated band gap that matched with the reported data. Also, the lattice parameters, interplanar distances, and Zn-O bond lengths were consistent with Joint Committee on Powder Diffraction Standards (JCPDS). Finally, a ZnO NP film was deposited on a steel substrate, which generated a displacement of 150 nm under a square wave voltage of 10 V. The piezoelectric behavior of the synthesized ZnO NPs can be useful for fabrication of piezoelectric nanogenerators. The proposed synthesis can allow ZnO NPs with potential application in electronic devices, energy harvesters, and transducers.